1988
DOI: 10.1038/bjc.1988.294
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of c-fgr protooncogene mRNA in Epstein-Barr virus converted cell lines

Abstract: Summary The c-fgr protooncogene is a member of the c-src family of tyrosine kinases. Expression of c-fgr was studied in a series of Epstein-Barr virus (EBV) negative Burkitt's lymphoma cell lines and their EBVconverted derivatives. Two transcripts, of 2.9kb and 3.5kb, were present at dramatically elevated levels following EBV-conversion.The structure of the c-fgr transcripts was studied by the isolation and nucleotide sequence analysis of cDNA clones. This indicated that the c-fgr protein encoded by the mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Actually, fgr mRNA was abundantly detected in terminally differentiated cells, such as normal circulating granulocytes and tissue macrophages. Fgr molecules were shown to be expressed also in EBV-infected B lymphocytes (7, 28) with a unique 5'-untranslated region which was not utilized in a myelomonocytic cell line (4,19). Further, the expression of c-fgr mRNA in the EBVinfected B cells appeared to be operated by the differential promoter utilization and alternative splicing (7).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, fgr mRNA was abundantly detected in terminally differentiated cells, such as normal circulating granulocytes and tissue macrophages. Fgr molecules were shown to be expressed also in EBV-infected B lymphocytes (7, 28) with a unique 5'-untranslated region which was not utilized in a myelomonocytic cell line (4,19). Further, the expression of c-fgr mRNA in the EBVinfected B cells appeared to be operated by the differential promoter utilization and alternative splicing (7).…”
Section: Discussionmentioning
confidence: 99%
“…pFal is a human c-fgr cDNA clone with an insert of 2156bp, extending from nucleotide 37 of the c-jgr coding region to nucleotide 607 of the 3' untranslated region. A restriction map of pFal, with its nucleotide sequence, has been published (Brickell and Patel, 1988). pCAl is an 800bp BglII-EcoRI genomic fragment encompassing the human immunoglobulin A light chain CAl constant region exon, cloned into pBR322 (Taub et al, 1983).…”
Section: Nuclear Run-off Assaysmentioning
confidence: 99%
“…Fgr is a member of the Src family of cytoplasmic protein tyrosine kinases, which also includes Fyn, Hck, Lck, Lyn, Tkl and Yes. These proteins are thought to be involved in intracellular signalling during the growth and differentiation of different cell types (Brickell and Patel, 1988). Fgr is expressed in mature peripheral blood monocytes and granulocytes, and in alveolar and splenic macrophages (Ley et al, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1]. In humans, the c-fgr gene is located at chromosome 1 p36.2-p36.1 [2], and genomic clones [3] and human [4][5][6] and murine [7,8] cDNA clones have been isolated. Nucleotide sequence analysis of these clones has shown that c-fgr is a member of a gene family which also includes c-src, fyn, hck, lek, lyn and c-yes [reviewed in ref .…”
Section: Introductionmentioning
confidence: 99%